Analisis Unsur Fisik dan Unsur Batin pada Puisi Aku Menemuimu Di Ujung Malam, Maqamat Cinta, Bersamamu Ketika Senja dan Bersama Syair Kenangan Karya Heri Isnaini (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Heri Isnaini's poetic works offer a profound beauty of language and meaning that needs to be analyzed. The purpose of this research is to analyze the physical and mental elements contained in the poem by Heri Isnaini entitled "I met you at the end of the road", "maqamat cinta", with you "at dusk" and "with the poem of memories". The method used in this analysis is a literature study method by collecting several relevant literature sources, including literary theories and poetry analysis, to support the understanding of the works being studied. The result of this analysis is that the inner element and the physical element have an influential role in building a work, especially in the poem by Heri Isnaini. The physical element in the form of diction, theme, and language structure provides aesthetic beauty, while the inner element contains messages, longing, and reflections on life that contain strong meaning and emotions. The conclusion of this study is that the inner and physical elements have an important role for literary works in building a beauty.